PROBLEMS OF HARMONIZING NATIONAL TRADITIONS AND MODERN TRENDS IN CLOTHING DESIGN (Multidisciplinary Journal of Science and Technology, 2025)
This article scientifically analyzes the issues of combining national traditions and modern trends in clothing design. Aesthetic symbols that express nationality, the specific characteristics of modern fashion trends, and their interaction are highlighted. It also presents the challenges and solutions to the challenges of combining traditional and innovative approaches in design.